7 - Social Protection Policymaking in Kenya: Power and Resistance in a Globalised World - Ouma, Marion (Africa Development, 2020)
Policymaking is no longer exclusively a national affair. Due to globalisation, global agendas easily influence and permeate national plans through policy transfer, diffusion and learning. One such recent global agenda is social protection policies in the form of cash transfers. Studies examining the process of adoption and making of such policies portray a benign learning approach. However, these approaches represent an incomplete view of the dynamics that characterise the adoption of policies. Social protection policymaking arenas are sites of power and resistance which are mutually constituted and exhibited through various forms. Drawing from the nexus of policy transfer and power, this article investigates the forms of power and resistance in the social protection policymaking space by examining the Cash Transfer for Orphans and Vulnerable Children (CT-OVC) and the Hunger Safety Net Programme (HSNP) in Kenya. The findings indicate that, as international actors attempted to impose their agendas, political elites resisted in two ways: firstly, by suppressing the action of other actors, and secondly, by asserting alternatives in the policy process. The findings suggest that even in enduring asymmetrical social relations, ‘subordinate’ actors in policy development arenas find space to exercise power through resistance, and exhibit the capacity to influence processes.